Editorial - unilibre, autor (Cultura del cuidado, 2018)
Nurse practitioners (NP) are healthcare professionals educated and trained to provide health promotion and maintenance through the diagnosis and treatment of acute illness and chronic conditions. According to the International Council of Nurses, an advanced practice registered nurse is “a registered nurse who has acquired the expert knowledge base, complex decision-making skills and clinical competencies for expanded practice, the characteristics of which are shaped by the context and/or country in which s/he is credentialed to practice. NPs complete advanced education (a minimum of a master’s degree) beyond basic education and licensing required of all registered nurses. The advanced education includes advanced physical assessment, diagnosis, interpretation of diagnostic tests, management of common medical conditions, including chronic illnesses and pharmacological therapies. NPs serve as primary care providers and they perform a broad range of healthcare services